Family firm internationalization: Influence of familiness on the Spanish firm export activity - Fernando Merino; Joaquín Monreal-Pérez; Gregorio Sánchez-Marín (Kiel Institute for the World Economy (IfW), 2012)
This paper studies the determinants of the export activity of family SMEs, disentangling the three main dimensions that comprise the concept of familiness: power, experience, and culture. The results, using the F-PEC scale over a sample of 500 Spanish SMEs, show that this approach identifies the determinants that explain the export activity of family SMEs better than a simple dichotomous approach. Specifically, we find that the expertise transmitted from different generations and the family culture orientation to the firm positively affect the international activities of family SMEs; however, the composition of the firm control-management does not have any significant influence on internationalization.
Keywords: D22; M16; 330; Family SMEs; Export activity; Familiness; Spanish firms; F-PEC scale; Familienunternehmen; KMU; Export; Multinationales Unternehmen; Schätzung; Spanien